2007
DOI: 10.1158/1078-0432.ccr-06-2088
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Cancer Cells and Stromal Fibroblasts Is Required for Activation of the uPAR-uPA-MMP-2 Cascade in Pancreatic Cancer Metastasis

Abstract: Purpose: Interaction between tumor cells and surrounding stromal fibroblast (SF) plays a critical role in tumor growth and invasion. The aim of the study is to determine the role of SF in regulating the invasive behaviors of pancreatic cancer by evaluating the mode of SF activating the urokinase plasminogen activator (uPA)-plasmin-matrix metalloproteinase (MMP)-2 cascade. Experimental Design: The expression patterns of uPA, MMP-2, and uPA receptor (uPAR) in human metastatic pancreatic cancer were analyzed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 38 publications
3
72
0
Order By: Relevance
“…33,34 Proteolytic mechanisms are indeed additional players involved in matrix remodeling and crucial roles of cysteine and serine proteases and their inhibitors have been recognized not only for tissue remodeling, but also for angiogenesis, stromal invasion, and formation of metastases by malignant cancer cells. 35,36 In this study, we have confirmed that TGF-b1 is expressed in chronically damaged hepatocytes, and we have shown for (a) TGF-b1 mRNA induction in HepG2, Huh7 cells, and primary human hepatocytes. TGF-b1 transcripts were assessed in each sample of transiently transfected cells at 48 h from the transfection with SERPINB3 (gray bars) or with the empty vector (white bars) by real-time PCR using primers specific for the human TGF-b1 gene.…”
Section: Discussionsupporting
confidence: 75%
“…33,34 Proteolytic mechanisms are indeed additional players involved in matrix remodeling and crucial roles of cysteine and serine proteases and their inhibitors have been recognized not only for tissue remodeling, but also for angiogenesis, stromal invasion, and formation of metastases by malignant cancer cells. 35,36 In this study, we have confirmed that TGF-b1 is expressed in chronically damaged hepatocytes, and we have shown for (a) TGF-b1 mRNA induction in HepG2, Huh7 cells, and primary human hepatocytes. TGF-b1 transcripts were assessed in each sample of transiently transfected cells at 48 h from the transfection with SERPINB3 (gray bars) or with the empty vector (white bars) by real-time PCR using primers specific for the human TGF-b1 gene.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, we were inclined to accept that the uPAR interaction with uPA and ␤1 integrins ultimately lead to the activation of matrix-degrading MMPs. Additionally, the uPAR/uPA interaction has been suggested to be involved in the activation of ECM-degrading MMP2 (32). To resolve whether uPAR contributed to invasion beyond that of MMPs, MT1-MMP in particular, we conducted another invasion assay where we co-treated H1299 cells with either 2G10 or 3C6 and the broad-spectrum MMP inhibitor GM6001 or an antibody against the catalytic domain of MT1-MMP.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic degradation of the extracellular matrix by tumor cell-secreted proteases, including plasminogen activators, serine proteinases, and matrix metalloproteinases (MMP), is important for tumor angiogenesis, invasion, and metastasis (1,2). Increased expressions of MMPs, particularly MMP-2 (gelatinase A; 72-kDa type IV collagenase) and MMP-9 (gelatinase B; 92-kDa type IV collagenase), have been intensely correlated with the malignancy of tumors and poor survival in patients, especially with breast cancer (3,4).…”
Section: Introductionmentioning
confidence: 99%